Effort-reward imbalance and burnout among humanitarian aid workers - Jachens, Liza; Houdmont, Jonathan; Thomas, Roslyn (Wiley, 2018)
Objectives: This study examined stress-related working conditions – defined in terms of effort-reward imbalance (ERI) – and its association with burnout among a large, international sample of humanitarian aid workers.